Bibliometric analysis of global media representations of marginalized groups - Li, Caiwei; Mohd. Nor Shahizan Ali; Ammar Redza Ahmad Rizal; Xu, Jingwen (Penerbit Universiti Kebangsaan Malaysia, 2024)
Over the years, the media have consistently influenced society and culture through the process of mediatization. Therefore, many public stereotypes regarding marginalized or vulnerable groups often originate from media discourse strategies. This study investigates the terms "marginalized groups," "media," and "representation" to perform a bibliometric analysis of 660 published articles from 2014 to 2023, concentrating on how the media portrays marginalized communities. The analysis covers essential metrics, including yearly publication rates, source journals, authorship, countries involved, and citation counts. Techniques such as keyword co-occurrence analysis, clustering analysis, and temporal evolution analysis are applied to summarize and assess the current landscape and future directions of this domain. The research utilizes the software tools POP (Publish or Perish) and VOSviewer to evaluate the present situation, identify research hotspots, and track the development within the field. In the past decade, research in this field has generally grown, with Western countries making significant contributions. The frequent occurrence of keywords highlights a strong focus on the media’s role in shaping public opinion and fostering inclusivity, using content analysis and adapting to current crises, such as COVID-19. The study identifies five main clusters: mass media, anthropology, public health, gender studies, and sexual minority health, showing the evolving diversity in media research on marginalized groups. Research progression spans three stages: the Preparatory Development Period (2014–2016), Growth Challenge Period (2017–2019), and Hotspot Research Period (2020–2023).